Toward Resilient Maternal, Neonatal and Child Health Care: A Qualitative Study Involving Afghan Refugee Women in Pakistan - Yasir Shafiq; Ameer Muhammad; Kantesh Kumar; Zabin Wajid Ali; Saba Noor; Zamir Hussain Suhag; Rehman Tahir; Abdullah Jan; Luca Ragazzoni; Francesco Barone-Adesi; Martina Valente (Health Services Insights)
Background: Afghan refugees in Pakistan, particularly in Quetta, Balochistan, encounter formidable barriers in accessing maternal, newborn, and child health (MNCH) services. These challenges have been intensified by the COVID-19 pandemic and entrenched systemic health inequities. Methods: This qualitative study, conducted from February to April 2023, aimed to assess the obstacles within health systems and community environments that hinder MNCH service access among Afghan refugees. The study involved 20 key informants through in-depth interviews and focus group discussions, including Afghan refugee women, community elders, health workers, and representatives from non-governmental organizations and government agencies. The research focused on experiences during the initial four waves of the COVID-19 pandemic (2020-2021), utilizing a conceptual framework integrating Health Emergency Disaster Risk Management (Health-EDRM) with primary health care. Findings: The study identified significant systemic barriers to accessing MNCH services, such as insufficient funding, inadequate health infrastructure, and discriminatory practices within the healthcare workforce. Additionally, community-level obstacles were prominent, including cultural and language differences, geographical isolation, and economic constraints. The integration of Health-EDRM into local health systems was minimal, with many stakeholders either needing to be made aware of or unengaged with the framework. Conclusion: The findings highlight a critical need for comprehensive policy reforms, infrastructure enhancement, and community-centered approaches to address Afghan refugees’ health needs effectively. Strengthening the integration of health-EDRM into health systems is crucial for enhancing resilience and ensuring continuous care during health emergencies. The study calls for concerted efforts to implement culturally sensitive health interventions that include disaster risk management components to improve MNCH outcomes among Afghan refugees in crisis-affected settings. Addressing systemic and community-level barriers makes creating a more resilient and equitable health system for vulnerable populations possible.